Chart Card: Feasibility of a Tool for Improving Emergency Department Care in Sickle Cell Disease - Neumayr, Lynne (J Natl Med Assoc, 2010)
BACKGROUND: Patients with sickle cell disease (SCD) are concerned with emergency department care, including time to treatment and staff attitudes and knowledge. Providers are concerned about rapid access to patient information and SCD treatment protocols. A software application that stores and retrieves encrypted personal medical information on a plastic credit card–sized Chart Card was designed. OBJECTIVE: To determine the applicability and feasibility of the Chart Card on patient satisfaction with emergency department care and provider accessibility to patient information and care protocols. METHODS: One-half of 44 adults (aged ~18 years) and 50 children with SCD were randomized to either the Chart Card or usual care. Patient satisfaction was surveyed pre and post implementation of the Chart Card program, and emergency department staff was surveyed about familiarity with SCD treatment protocols. RESULTS: Fifty-two percent of patients were female (mean age, 18.8 ± 15.6); 61% had SCD SS. Adults visited an emergency department 4.2 ± 4.0 times in the year prior to enrollment vs 2.7 ± 3.7 (p = .06) visits for children, most commonly for pain. Patient emergency department care ratings of very good or excellent increased from 47% to 66% (p < .05), and ratings of staff knowledge improved. Qualitative data reflected positive comments about patient and staff experiences with the Chart Card. CONCLUSION: Patient satisfaction with emergency department care and efficacy in health care increased post Chart Card implementation. Providers valued immediate access to patient information and SCD treatment guidelines. The technology has potential for application in the treatment of other illnesses in other settings.